Conformer Distribution in Rotaxanes Containing Nonsymmetric Threads: A Systematic Approach. Issue 36 (21st August 2018) - Orlando, Tainára; Salbego, Paulo R. S.; Zimmer, Geórgia C.; Pagliari, Anderson B.; Bender, Caroline R.; Rodrigues, Leticia V.; Bonacorso, Helio G.; Zanatta, Nilo; Berná, Jose; Martins, Marcos A. P.
Abstract : Rotaxanes are designated as molecular machines due their different movements. Systematic studies regarding the different conformations adopted by these systems and the factors that lead to the distribution of the conformations, in both solution and the solid state, have not been widely explored, especially for rotaxanes with nonsymmetric stoppers. Therefore, in this study we have investigated three novel [2]rotaxanes containing threads derived from nonsymmetric succinamides [R 1 R 2 NC(O)‐CH2 CH2 ‐C(O)NR 2 R 1, with R 1 /R 2 = Bu/Bn, Bu/2‐furylmethyl, and 5‐methylisoxazol‐3‐yl/2‐furylmethyl]. The proportions of rotamers were investigated for threads and rotaxanes by solution and solid‐state NMR spectroscopy as well as by single‐crystal and powder X‐ray diffraction. In solution, the threads present different proportions of conformer, with the E, Z conformation prevailing, whereas only one conformer is observed in the solid state. For the rotaxanes, only one conformer prevails in the single crystal, whereas the solution and solid (bulk) states present more than one rotamer. These proportions are modified when the threads are incorporated into the macrocycle during rotaxane formation. The intramolecular interactions in each rotamer were investigated by QTAIM and variable‐temperature 1 H NMR experiments. The changes in conformational population between the threads and respective rotaxanes can be explained by a set of different intramolecular interactions, with trifurcated hydrogen bonds responsible for most of the stabilization energy. Abstract : A conformational study of rotaxanes has been performed. The proportion of different rotamers was investigated for threads and for threads incorporated into rotaxanes. This investigation was performed by using solution and solid‐state NMR spectroscopy, single‐crystal XRD, and PXRD. How the conformational population is affected when the thread is incorporated into the macrocycle has been evaluated.